Effect of administration of two commercial formulations based on bovine recombinant somatotropin on the productive and economic performance of dairy cows - Melo, Waldjânio de Oliveira; Souza, Lennon Higor Cardoso de; Oliveira, Yuri Silva; Souza, Fabricio Teixeira; Monteiro, Bruno Moura (Revista de Ciências Agroveterinárias, 2025)
The aim of this study was to evaluate the effect of administering two commercial formulations based on recombinant bovine somatotropin (rbST) on the performance of dairy cows. Fifty-four Girolando cows were used, distributed across three treatments. The first group (n=17) received 500 mg of Sometribove zinc (1.4 ml of Lactotropin® Elanco) every 14 days. The second group (n=19) received 500 mg of rbST (2 ml of Boostin® MSD Animal Health) every 14 days. The third group (n=18) did not receive rbST (control). Milk production was measured every ten days, from 109 to 172DIL, twice a day at 12-hour intervals. Milk production was evaluated as a repeated measure over time, referring to the moments of data collection (time) according to each treatment, as well as the Treatment*Time interaction, using the Repeated command generated by the Mixed procedure of SAS. The SAS LSMeans mean test was used to compare treatments, using the SAS Glimmix procedure. It was found that there was no statistical difference between cows that received Lactotropin® and those in the Boostin® group; however, both showed superior results compared to the control group. The average increase in production with Boostin compared to the control was 3.74 L/cow/day, while Lactotropin was 3.29 L/cow/day. Considering the values of each dose, R$18.50 and R$33.00 respectively, and the sale price per liter of milk produced of R$2.05. We can see from the results obtained that Boostin provides a profit margin of R$6.35/cow/day for every R$1.32 invested. While Lactotropin requires an investment of R$2.36, generating a profit margin of R$4.39/cow/day. Therefore, the most viable option to use will be Boostin, which has a lower commercial value, generating a higher profit margin.